2016
DOI: 10.1111/bjh.13898
|View full text |Cite
|
Sign up to set email alerts
|

Review: Aberrant EVI1 expression in acute myeloid leukaemia

Abstract: Deregulated expression of the ecotropic virus integration site 1 (EVI1) gene is the molecular hallmark of therapy-resistant myeloid malignancies bearing chromosomal inv(3)(q21q26·2) or t(3;3)(q21;q26·2) [hereafter referred to as inv(3)/t(3;3)] abnormalities. EVI1 is a haematopoietic stemness and transcription factor with chromatin remodelling activity. Interestingly, the EVI1 gene also shows overexpression in 6-11% of adult acute myeloid leukaemia (AML) cases that do not carry any 3q aberrations. Deregulated e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 67 publications
2
43
0
2
Order By: Relevance
“…However, the expression of the protein products of these fusion transcripts in primary leukemic cells has not yet been documented, to the best of our knowledge. In the present study, it was confirmed that the fusion products were expressed in present patient at a high level, comparable to that of EVI1 in human leukemic MOML-1 cells with inv(3) (q21.2;q26) (7,9) and HEL cells (32). The Runt domain maintained in AME is the DNA-binding domain of RUNX1, which is the DNA-binding subunit of the core-binding transcription factor that regulates the expression of genes essential for hematopoiesis.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, the expression of the protein products of these fusion transcripts in primary leukemic cells has not yet been documented, to the best of our knowledge. In the present study, it was confirmed that the fusion products were expressed in present patient at a high level, comparable to that of EVI1 in human leukemic MOML-1 cells with inv(3) (q21.2;q26) (7,9) and HEL cells (32). The Runt domain maintained in AME is the DNA-binding domain of RUNX1, which is the DNA-binding subunit of the core-binding transcription factor that regulates the expression of genes essential for hematopoiesis.…”
Section: Discussionsupporting
confidence: 84%
“…EVI1 also exists as the fusion protein MDS1/EVI1 (ME), which is generated by the alternative splicing of the third exon of MDS1 to the second exon of EVI1 with the two genes located nearby to form the MDS1-EVI1 complex locus ( MECOM ) on 3q26.2 (6,7). The most common types of 3q26.2 abnormalities are inv (3) (q21q26.2)/t(3;3)(q21;q26.2), which define a category of AML in the WHO classification and relocate a distal enhancer of the GATA binding protein 2 ( GATA2 ) gene to a region between MDS1 and EVI1 , which ectopically activates EVI1 (1,7,9,10). In contrast, t(3;21)(q26.2;q22) results in the translocation of a part of RUNX1 at 21q22 to MECOM and generates various fusion transcripts (2,4).…”
Section: Introductionmentioning
confidence: 99%
“…30 MECOM is involved in numerous rearrangements leading to overexpression or formation of fusion transcripts with RUNX1 or ETV6 in myeloid malignancies. 31 The role of MECOM in human hematopoiesis is emphasized by the phenotype of the patients in this study; all patients were affected by thrombocytopenia, and most of them developed hypoplastic BM and pancytopenia. Our experiments, together with published data, strongly suggest an impaired maintenance of hematopoietic stem cells as the reason; we were able to demonstrate a severe reduction of early CD34…”
Section: Discussionmentioning
confidence: 69%
“…Although that study was based on the detection of DNA copy number, it still reflects the controversial role of EVI1 in some special cancer types 19. In conclusion, many studies20,21 identified EVI1 as a protein promoting cancer progression, but consensus has not been reached. More experiments need to be performed for validation if new cancer types are involved, such as SCC.…”
Section: Discussionmentioning
confidence: 96%